Dalia Gargasaitė - bibliografė ir knygotyrininkė - Mačiulis, Jonas (Knygotyra, 1999)
Dalia Gargasaitė (1938-1998) is considered to be one of the most distinguished contemporary bibliographers and book science specialists of Lithuania. Since the beginning of her creative work in the field of book science (she wrote a thesis titled "Dual Number in the Present-Day Lithuanian Language"), later on, being a staff member of the Lithuanian Book Chamber (now the Centre of Bibliography and Book Science within the Martynas Mažvydas National Library of Lithuania), she became famous as a researcher of old Lithuanian publications. She is a co-author of the fundamental work of Lithuanian bibliography of Series A, "Books in Lithuanian" (vol. I, 1969; vol. II (1), 1985; vol. II (2), 1988; vol. I: supplements, 1990). The object of investigations of the late D. Gargasaitė was Lithuanian books published in the United States between 1874 and 1904. Her exhaustive and generalized article on Lithuanian books in the US of that period is the first and most comprehensive work on this subject in Lithuania to date. During the last decade, she examined the publishing situation of Lithuanian books in the United States during the years 1905-1917. Concurrently, she actively participated in the preparation of the Lithuanian bibliographic publication of Series C titled "Articles from the Lithuanian Periodicals," which includes the period of 1832-1890. D. Gargasaitė is a compiler of the poetry collections "The Dawn is Coming, the New Day is Breaking" (1977) and "A Rustic’s Song" (1982), which present samples of anonymous poetry from the 16th-19th centuries, as well as revolutionary poetry from the end of the 19th and beginning of the 20th centuries. D. Gargasaitė actively participated in both scientific and periodical press. She made annotations and descriptions of the lithuanistically significant publications found in foreign libraries and archives, revealing the real names of authors writing under pseudonyms. In addition, she constantly raised the urgent problems of bibliographing old publications, publishing articles regarding Lithuanian cultural figures and press activists. For example, she wrote an article about the traveler and disseminator of Lithuanianism, Matas Šalčius. During the last decade of her life, D. Gargasaitė devoted the greatest attention in her publicistic writings to the promulgation of the undertakings and accomplishments of cultural activists living in emigration, reflecting their efforts to cherish and foster Lithuanianism. She was a committed member of the Lithuanian Bibliophiles Society and was actively involved in the pursuits of the Lithuanian-Finnish and Lithuanian-Czech societies, delivering reports on book science at both national and international conferences.